"Delegation and Then Intervention": The 2009 Decision to Create the New Rural Pension. (10th November 2017) - Choi, Eun Kyong
Abstract: This article reviews the decision-making process behind the creation of a new rural pension between the early 2000s and 2009. It finds that although policymaking was initially delegated to the bureaucratic level and hence involved a protracted bureaucratic struggle, the issue was resolved by a fiat imposed by top leaders rather than by bureaucratic compromise as a bureaucratic politics model would suggest. I call this policymaking process "delegation and then intervention." Although the Ministry of Labour and Social Security (MOLSS) persistently argued in favour of creating the new rural pension, the Ministry of Finance obstinately objected to it. This study finds that when bureaucratic organizations are in conflict because of their core beliefs, rather than resource allocation, they are less likely to reach a consensus. Faced with a prolonged bureaucratic deadlock, top leaders decided in favour of the MOLSS policy initiative, thereby adopting a progressive measure that would provide a completely subsidized basic pension for the rural elderly. 摘要: 本文是针对从 2000 初开始持续到 2009 年, "新型农村养老保险的施行" 这一公共政策制定过程的研究。研究发现初始阶段是在官僚层进行委任, 并伴随着官僚组织间严重的意见分歧。虽然这一政策制定过程中展示了官僚政治模式, 但这项政策的产生并不是官僚间妥协的产物, 而是主要依据最高领导层的决定。笔者将这一政策制定过程叫做 "先委任后介入" 模式。中国劳动和社会保障部是主张要施行新型农村养老保险, 但同时财政部一直很反对。这不是官僚组织间的资源分配, 而是针对信念出现意见分歧时, 协商会变得更难的主张也同样适用于这个案例。官僚组织间的意见分歧导致这一政策制定过程始终处于胶着状态, 最终因为最高领导层的介入, 使得偏向于劳动与社会保障部的政府决定建立有财政支持的, 包含基础养老金的新型农村养老保险制度.